Legal Protection For Children In Conflict With The Law Through Virtual Courts: Implementation Of The United Nation Convention On The Rights Of The Child. - Rizki Adi Pinandito; R Sugiharto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
AbstractThe conventional juvenile justice system has a bad impact on children's lives. The negative effects continue after the child is sentenced to a sentence, such as continuous stigma, trauma until the child is expelled from school which then has an impact on dropping out of school. This study aims to determine how the legal protection of the rights of children who are in conflict with the law based on positive law in Indonesia and the United Nations Convention On The Rights Of The Child and how the urgency of virtual justice can be an alternative juvenile justice in Indonesia. This research was conducted using a literature study method through juridical analysis with a normative juridical approach. From the results of the study, it was found that positive law in Indonesia has provided regulations regarding legal protection of the rights of children who are in conflict with the law. Virtual justice can be an alternative model for implementing courts for children and still be able to maintain the dignity of children.